Finite-time event-triggered consensus control for high-speed train with gradient resistance. Issue 2 (January 2022) - Su, Shuai; Han, Liange; Li, Shukai
Abstract: Regarding the influence of the gradient resistance on multiple electric units, this paper investigates the finite-time event-triggered consensus control for a single high speed train. By considering the influence of the internal force of the train and the non-linear resistance, a multi-particle model of electric multiple units is established, in which the electric units are connected by elastic couplers. Based on the principle of event-triggered control, a consensus control strategy for electric multiple units is designed, which has disturbance rejection property and does not need continuous communication between electric units, hence effectively saving plenty of computing and communication resources. By using finite-time Lyapunov stability theorems to improve the event-triggered controller, it is found that finite-time consensus presents a fast convergence rate and good anti-interference performance. The stability of the control system is verified by Lyapunov function, where all electric units of high-speed train achieve finite-time consensus and exclude Zeno behavior. Finally, the effectiveness of the theoretical results is verified by two numerical simulations.